What it takes seven secrets of success from the world's greatest professional firms - Ellis, Charles D. (Gildan Audio, 2020)
What It Takes is the distillation of lessons learned during nearly half a century of working backstage with the leaders of major professional firms as a trusted adviser on strategy and management, observing a few firms rise deliberately to leadership while many others with comparable hopes could not. Over and over again, in dozens of private meetings with firm leaders, the core questions were: Why do some firms rise to leadershipand why do most not make it' What does it take to excel' Perhaps even more important, what does it take to sustain excellence over years and decades, through success and adversity' Experience teaches that in a competitive market, organizations can rise to acknowledged leadership only by excelling in several specific areas: defining a compelling organizational mission and developing a strong complementary culture; consistently recruiting clearly superior people and training them intensively; organizing and motivating them to work in effective teams devoted to serving important clients on their most important problems; and continuously finding new and better ways, both large and small, to deliver distinctive value for clients. The extensive research for this book is based on decades of studying the success and failure of hundreds of professional firms in North America, Europe and Asia, and on over 300 formal interviews with the past and current leaders of the five extraordinary professional firms that exemplify the elements of durable excellenceMcKinsey in consulting, Cravath, Swaine & Moore in law, Goldman Sachs in investment banking, Capital Group in investment management and Mayo Clinic in health care.